2020
DOI: 10.1088/1742-6596/1480/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of creative problem-solving models on students’ higher level thinking skills in linear programming

Abstract: The purpose of this study was to determine the effect of Creative Problem Solving (CPS) on Higher Level Thinking Skills of Grade XI students in High Schools in Linear Programs. This research was carried out in SMA Negeri 5 Palembang. This research method is quantitative with only a control group posttest design. Regarding the experimental class will be given with Creative Problem Solving while the control class will be given with cooperative learning. High-level Thinking Skills are postal measurements and data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Amongst the studies that reported the age of participants, the range was between 13 and 18 years. Two studies (25%) were conducted in Taiwan (Chen et al, 2021; Wang, 2019), three (27.5%) in Indonesia (Adila et al, 2020; Julita et al, 2019; Pratiwi et al, 2021), one (12.5%) in Turkey (Islim & Karatas, 2016), one (12.5%) in Portugal (Azevedo, de Fátima Morais, & Martins, 2019), with the remaining study failing to report its geographical location (Hidayati et al, 2021). The research was conducted across both public high schools and independent schools, and a large number of subject classes were incorporated, including sciences (25%), ICT (12.5%), mathematics (12.5%), and English (12.5%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Amongst the studies that reported the age of participants, the range was between 13 and 18 years. Two studies (25%) were conducted in Taiwan (Chen et al, 2021; Wang, 2019), three (27.5%) in Indonesia (Adila et al, 2020; Julita et al, 2019; Pratiwi et al, 2021), one (12.5%) in Turkey (Islim & Karatas, 2016), one (12.5%) in Portugal (Azevedo, de Fátima Morais, & Martins, 2019), with the remaining study failing to report its geographical location (Hidayati et al, 2021). The research was conducted across both public high schools and independent schools, and a large number of subject classes were incorporated, including sciences (25%), ICT (12.5%), mathematics (12.5%), and English (12.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Adila et al also employed an adapted CPS model, the Pepkin's CPS model. This model is devised for problem clarification, brainstorming, evaluation and selection, and implementation (Adila et al, 2020). A similar model, the SCAMPER technique, was employed by Islim and Karatas (2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sebagai sebuah sistem, matematika memiliki sejumlah definisi dan aturan yang harus dipatuhi untuk memperoleh hasil yang benar (Adila, Hartono, Indaryanti, Scristia, & Yusup, 2020;Selvia, Hartono, Indaryanti, Scristia, & Yusup, 2020). Kebenaran sebuah pernyataan matematika dianggap sebagai konsekuensi logis dari definisi, aksioma, atau pernyataanpernyataan lain yang sebelumnya sudah dibuktikan benar.…”
Section: Hasil Dan Pembahasanunclassified